2019
DOI: 10.4049/jimmunol.1900101
|View full text |Cite
|
Sign up to set email alerts
|

Cytokine Diversity in Human Peripheral Blood Eosinophils: Profound Variability of IL-16

Abstract: to H.F.R.). M.M. performed most of the experimental work, optimized the eosinophil isolation and cytokine profiling, coordinated the donor samples with the National Institutes of Health Clinical Center Blood Bank, and reviewed the methods for the manuscript. C.M.P. performed additional experimental work and provided input on the first draft of the manuscript. D.E.S. performed multivariate analysis of the cytokine profiling data and reviewed the revised manuscript. A.C.S. assisted with experimental work and pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(17 citation statements)
references
References 84 publications
1
16
0
Order By: Relevance
“…The induction of other cytokines (IL-2, IL-4, IL-15, IL-22, IL-10, IL-12, and IL-21) was also observed ( Figure S3); in some cases (e.g., IL-2 and IL-15), the induction was donor-dependent suggesting that individual variability in NANP-mediated cytokine signaling including the expression of receptors involved in NANP recognition exists. Such interindividual variability is not surprising since both qualitative and quantitative variations in individuals' immune responses have been described before [57][58][59][60][61].…”
Section: Discussionmentioning
confidence: 82%
“…The induction of other cytokines (IL-2, IL-4, IL-15, IL-22, IL-10, IL-12, and IL-21) was also observed ( Figure S3); in some cases (e.g., IL-2 and IL-15), the induction was donor-dependent suggesting that individual variability in NANP-mediated cytokine signaling including the expression of receptors involved in NANP recognition exists. Such interindividual variability is not surprising since both qualitative and quantitative variations in individuals' immune responses have been described before [57][58][59][60][61].…”
Section: Discussionmentioning
confidence: 82%
“…Bulk analysis of the granule cytokine contents within blood eosinophils from healthy donors revealed that eosinophils emerge from the bone marrow already stocked with a highly diverse cache of cytokines associated with Th1-, Th2- and regulatory functions, which are rapidly and differentially secreted in response to alterations in the cytokine milieu [ 49 ]. Relative concentrations of several of these preformed, granule-stored cytokines appear to be remarkably well conserved across different subjects (e.g., IL-5, IL-4 and IL-13), while other preformed cytokines exhibited moderate (e.g., IFN-γ, IL-8 and IL-10) or profound (e.g., IL-16) variability between individuals [ 50 , 51 ]. Applying cluster analysis, Ma etal.…”
Section: Eosinophil Heterogeneitymentioning
confidence: 99%
“…Applying cluster analysis, Ma etal. demonstrated at least some eosinophil-associated cytokines (e.g., IL-1β, IL-1α and IL-6) appear to be coordinately regulated [ 51 ]. How the preformed cytokine repertoire is shaped in human blood eosinophils remains elusive; however, eosinophil IL-16 content in a subset of normal donors correlated with body mass index [ 51 ], suggesting systemic metabolic factors may contribute to eosinophil cytokine profiles.…”
Section: Eosinophil Heterogeneitymentioning
confidence: 99%
See 1 more Smart Citation
“…While eosinophils have been implicated in energy homeostasis and regulation of adipose tissue, the underlying mechanisms and associated outcomes remain controversial [ 13 18 ]. Recent studies documenting eosinophil heterogeneity have emphasized the diversity and functional versatility of this leukocyte subpopulation and have focused on the influence of both environment and location on the eosinophil phenotype [ 19 25 ]. Collectively, these findings represent an important extension of the LIAR hypothesis [ 26 ] as they suggest that eosinophils not only promote local immunomodulation, they may also be influenced by specific conditions in the microenvironment.…”
Section: Introductionmentioning
confidence: 99%